Differences in gonadal tissue cryopreservation practices for differences of sex development across regions in the United States - Siebert, Aisha L.; Gomez-Lobo, Veronica; Johnson, Emilie K.; Nahata, Leena; Orwig, Kyle E.; Pyle, Louise C.; Witchel, Selma F.; Finlayson, Courtney; Laronda, Monica M. (Frontiers in Endocrinology, 2023)
Objective: Some individuals with differences of sex development (DSD) conditions undergo medically indicated prophylactic gonadectomy. Gonads of individuals with DSD can contain germ cells and precursors and patients interested in future fertility preservation and hormonal restoration can participate in DSD-specific research protocols to cryopreserve this tissue. However, it is unclear how many providers or institutions offer gonadal tissue cryopreservation (GTC) and how widespread GTC for DSD is across the United States (US). The Pediatric Initiative Network (PIN) and Non-Oncologic Conditions committees of the Oncofertility Consortium sought to assess the current state of GTC for patients with DSD. Methods: An electronic survey was sent to providers caring for patients with DSD via special interest groups of professional societies and research networks. Results: The survey was administered between November 15, 2021 and March 14, 2022. A total of 155 providers responded to the survey, of which 132 respondents care for patients with DSD, and 78 work at facilities that offer medically indicated gonadectomy to patients with DSD diagnoses. They represented 55 US institutions including 47 pediatric hospitals, and 5 international sites (Canada, Denmark, Germany, Qatar). Of individual providers, 41% offer cryopreservation after prophylactic gonadectomy for patients with DSD (32/78). At an institutional level, GTC after medically indicated gonadectomy is available at 54.4% (25/46) institutions. GTC is offered for a variety of DSD diagnoses, most commonly 45,X/46,XY DSD (i.e., Turner Syndrome with Y-chromosome material and mixed gonadal dysgenesis), ovotesticular DSD, complete androgen insensitivity syndrome (CAIS), and complete gonadal dysgenesis. Responses demonstrate regional trends in GTC practices with 83.3% of institutions in the Midwest, 66.7% in the Northeast, 54.6% in the West, and 35.3% in the South providing GTC. All represented institutions (100%) send gonadal tissue for pathological evaluation, and 22.7% preserve tissue for research purposes. Conclusions: GTC after gonadectomy is offered at half of the US institutions represented in our survey, though a minority are currently preserving tissue for research purposes. GTC is offered for several DSD conditions. Future research will focus on examining presence and quality of germ cells to support clinical decision making related to fertility preservation for patients with DSD.